Production Jelly Candy and Soap derived from marine seaweed for health branding and community empowerment in Mojokerto East Java - Pujiastuti, Dwi Yuli; Sahidu, Adriana Monica; Nirmala, Dwitha (Kontribusia : Research Dissemination for Community Development, 2025)
In this PKM program, our partner is residents in Mojokerto, Surabaya, East Java, Province. This community has generated the production of jelly candy and natural soap derived from marine seaweed. Seaweed processing has a very broad market potential due to the increasing demand and use of seaweed processing products, both in the fields of food, health, cosmetics, pharmaceuticals or industry. Seaweed development with an industrial concept approach that starts from upstream, processing basic products into formulated products with a lot of derivative products, both food and non-food products. In food ingredients, seaweed can be formulated into jelly candy that is in great demand from children to adults. In pharmaceutical grade, it can be formulated into cosmetics such as natural soap. Based on interviews and observations in the field, there are 3 main focuses of the problems currently faced by partners, namely: 1) lack of knowledge about seaweed, 2) seaweed application for food and non-food and 3) the packaging of product. Some of the things planned by the PKM team are innovating seaweed to be jelly candy and natural soap. The purpose of this activity is to provide knowledge and understanding of the diversification of processed seaweed products for both food and non-food purposes, which is expected to provide benefits in terms of increasing the added value of seaweed, awareness of hand washing hygiene, empowering women and at the same time increasing community income. This activity was realized with an approach in the form of making a sustainable cooperation program until the end of PKM, creating a family atmosphere between the two and understanding that the problems experienced were a shared problem so that they could be solved together according to the level of responsibility to achieve the expected benefits, namely increased yields, production and productivity and competitiveness, independence and welfare of the community.